Risk factors for multidrug‐resistant Gram‐negative infection in burn patients. Issue 5 (29th August 2017) - Vickers, Mark L.; Dulhunty, Joel M.; Ballard, Emma; Chapman, Paul; Muller, Michael; Roberts, Jason A.; Cotta, Menino O.
Abstract : Background: Infection with multidrug‐resistant (MDR) Gram‐negative organisms leads to poorer outcomes in the critically ill burn patient. The aim of this study was to identify the risk factors for MDR Gram‐negative pathogen infection in critically ill burn patients admitted to a major tertiary referral intensive care unit (ICU) in Australia. Methods: A retrospective case–control study of all adult burn patients admitted over a 7‐year period was conducted. Twenty‐one cases that cultured an MDR Gram‐negative organism were matched with 21 controls of similar age, gender, burn size and ICU stay. Multivariable conditional logistic regression was used to individually assess risk factors after adjusting for Acute Burn Severity Index. Adjusted odds ratios (ORs) were reported. P ‐values < 0.25 were considered as potentially important risk factors. Results: Factors increasing the risk of MDR Gram‐negative infection included superficial partial thickness burn size (OR: 1.08; 95% confidence interval (CI): 1.01–1.16; P ‐value: 0.034), prior meropenem exposure (OR: 10.39; 95% CI: 0.96–112.00; P ‐value: 0.054), Gram‐negative colonization on admission (OR: 9.23; 95% CI: 0.65–130.15; P ‐value: 0.10) and escharotomy (OR: 2.66; 95% CI: 0.52–13.65; P ‐value: 0.24). For cases, mean age was 41 (SD: 13) years, mean total body surface area burned was 47% (SD: 18) and mean days in ICU until MDR specimen collection was 17 (SD: 10) days. Conclusion: Prior meropenem exposure, Gram‐negative colonization on admission, escharotomy and superficial partial thickness burn size may be potentially important factors for increasing the risk of MDR Gram‐negative infection in the critically ill burn patient.